2017
DOI: 10.1039/c7tc00631d
|View full text |Cite
|
Sign up to set email alerts
|

The optical and electronic properties of graphene quantum dots with oxygen-containing groups: a density functional theory study

Abstract: The effects of five types of oxygen-containing functional groups (–COOH, –COC–, –OH, –CHO, and –OCH3) on graphene quantum dots (GQDs) are investigated using time-dependent density functional theory (TD-DFT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 47 publications
2
86
0
Order By: Relevance
“…The large hybridization of HOMO and LUMO levels results in the reduction of the H-L gap in accordance with C 123 QDs functionalized using oxygen containing groups. 28 Additionally, it is clear that the HOMO and LUMO levels of both -CH 3 and -OH edgefunctionalized structures shi toward higher energies with respect to pyrene, while they shi toward lower energies in COOH-CQDs. This nding can be assigned to the presence of the double bond in the COOH functional group.…”
Section: Electronic Propertiesmentioning
confidence: 98%
See 2 more Smart Citations
“…The large hybridization of HOMO and LUMO levels results in the reduction of the H-L gap in accordance with C 123 QDs functionalized using oxygen containing groups. 28 Additionally, it is clear that the HOMO and LUMO levels of both -CH 3 and -OH edgefunctionalized structures shi toward higher energies with respect to pyrene, while they shi toward lower energies in COOH-CQDs. This nding can be assigned to the presence of the double bond in the COOH functional group.…”
Section: Electronic Propertiesmentioning
confidence: 98%
“…26) and, (ii) C 123 H 38 QDs functionalized with oxygen containing groups. 28 Accordingly, upon functionalization, the H-L gap drops by 9.1-23.14% for CQDs since -CH 3 functionalized structures possess the highest H-L gap while the lowest gap is that of -COOH. For SiQDs, carboxylation resulted in decreasing the H-L gap due to the existence of the C]O double bonds in the -COOH molecules.…”
Section: Electronic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a question if these conditions can be realized in carbonic nanostructures. However, theoretical studies have shown the possibility of generating the loosely bound excitons in graphene nanoscale monolayers with the inclusion of polar groups at the sheet edges [205,206]. The evidence for their presence was obtained in experiments on graphene oxide sheets [207].…”
Section: On the Involvement Of Wannier-mott Loosely Bound Excitonsmentioning
confidence: 99%
“…23 Consequently, the control of the preparation conditions as well as the choice of the manufacturing process opens the gap and tunes the optical properties of these nanostructures. 24,25 In parallel, the theoretical calculations have proven that many factors, namely; the size, the shape such as triangular and hexagonal, the edge conguration (zigzag/armchair), 26,27 the atom type, 28 the application of the electric eld, the chemical modication 29,30 which includes adsorption, substitution 31 as well as functionalization, 32,33 have a great impact on the optoelectronic properties and chemical reactivity of QDs. Indeed, they tailor the highest occupied-lowest unoccupied molecular orbital (HOMO)-(LUMO) energy gap.…”
Section: Introductionmentioning
confidence: 99%